Evaluation of the positive predictive value of a rapid Immunochromatographic test to detect Campylobacter in stools - Floch, Pauline (BioMed Central, 2012)
The recently developed rapid immunochromatographic tests (ICT) have the potential to provide a quick and easy diagnosis of Campylobacter enteritis in comparison to culture. In a previous study we found them sensitive but lacking in specificity. The aim of the present study was to focus on the problem of specificity and determine the positive predictive value (PPV) of a positive result of the ImmunoCard Stat! Campy (Meridian Bioscience, Cincinnati, OH, USA). For this purpose, the stools positive by ICT were cultured according to 3 different protocols: Karmali agar, Preston enrichment broth subcultured on Karmali agar, and a filtration method on a blood agar without antibiotics, all incubated for 7 days at 37°C. Out of 609 stools from adults and children with community acquired enteritis, the reference methods detected 25 positive cases (4.1%) (culture: 19, specific PCR and ELISA both positive: 6) and the ICT: 31 including the 25 true positives. The PPV was 80.6%. We conclude that ICT is a good method to screen Campylobacter positive stools but because of its lack of specificity the positive stools must be tested by another method.